Chaophilic or chaotolerant fungi: a new category of extremophiles? - Zajc, Janja; Džeroski, Sašo; Kocev, Dragi; Oren, Aharon; Sonjak, Silva; Tkavc, Rok; Gunde-Cimerman, Nina (Frontiers in Microbiology, 2014)
It is well known that few halophilic bacteria and archaea as well as certain fungi can grow at the highest concentrations of NaCl. However, data about possible life at extremely high concentrations of various others kosmotropic (stabilizing; like NaCl, KCl and MgSO4) and chaotropic (destabilizing) salts (NaBr, MgCl2 and CaCl2) are scarce for prokaryotes and almost absent for the eukaryotic domain including fungi. Fungi from diverse (extreme) environments were tested for their ability to grow at the highest concentrations of kosmotropic and chaotropic salts ever recorded to support life. The majority of fungi showed preference for relatively high concentrations of kosmotropes. However, our study revealed the outstanding tolerance of several fungi to high concentrations of MgCl2 (up to 2.1 M) or CaCl2 (up to 2.0 M) without compensating kosmotropic salts. Few species, for instance Hortaea werneckii, Eurotium amstelodami, Eurotium chevalieri and Wallemia ichthyophaga, are able to thrive in media with the highest salinities of all salts (except for CaCl2 in the case of W. ichthyophaga). The upper concentration of MgCl2 to support fungal life in the absence of kosmotropes (2.1 M) is much higher than previously determined to be the upper limit for microbial growth (1.26 M). No fungal representatives showed exclusive preference for only chaotropic salts (being obligate chaophiles). Nevertheless, our study expands the knowledge of possible active life by a diverse set of fungi in biologically detrimental chaotropic environments.